Selection index for rubber tree - Vasconcellos, Maria Elizabeth da Costa; Gonçalves, Paulo de Souza; Valois, Afonso Celso Candeira; Abreu, Clóvis Pompilo de (Pesquisa Agropecuaria Brasileira, 2014)
Utilizing nine characters concerned to plant vigor, and to the lacticiferous system, a selection index for rubber tree (Hevea spp) was established. A 5 x 5 triple lattice design with six plant per plot was considered in this study. The estimated selection index showed negative value for the plant height and average of whorls length. That result showed certain advantage for selection of short plants.